2022
DOI: 10.3389/fimmu.2021.810602
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-27 in Tuberculosis: A Sheep in Wolf’s Clothing?

Abstract: In tuberculosis (TB), protective inflammatory immune responses and the pathological sequelae of chronic inflammation significantly depend on a timely balance of cytokine expression. In contrast to other anti-inflammatory cytokines, interleukin (IL)-27 has fundamental effects in experimental Mycobacterium tuberculosis (Mtb) infection: the absence of IL-27-mediated signalling promotes a better control of mycobacterial growth on the one hand side but also leads to a chronic hyperinflammation and immunopathology l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 122 publications
(210 reference statements)
0
3
0
Order By: Relevance
“…Male control mice exhibited significantly lower IFN-γ but higher IL-27 levels compared to females. IFN-γ is essential to control TB infection [29,30], whereas IL-27 has been previously shown to exhibit a double-edged sword effect: suppressing protective immunity against TB and bacterial clearance, while simultaneously dampening excessive inflammation [28,31,32]. Studies using mice deficient in WSX-1, a component of the IL-27 receptor, revealed increased activation of CD4 + T cells and IFN-γ production [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Male control mice exhibited significantly lower IFN-γ but higher IL-27 levels compared to females. IFN-γ is essential to control TB infection [29,30], whereas IL-27 has been previously shown to exhibit a double-edged sword effect: suppressing protective immunity against TB and bacterial clearance, while simultaneously dampening excessive inflammation [28,31,32]. Studies using mice deficient in WSX-1, a component of the IL-27 receptor, revealed increased activation of CD4 + T cells and IFN-γ production [32].…”
Section: Discussionmentioning
confidence: 99%
“…IL-27, like IL-10, is an important anti-inflammatory cytokine that has a dual role in TB. On the one hand, IL-27 limits protective immunity to Mtb but on the other hand it prevents from excessive inflammation and immunopathology [28]. Thus, we next evaluated the granulomatous response in absence of B cellderived IL-10, which led to a significant reduction in IL-27 levels in males (see Fig.…”
Section: Histopathological Changes In Lung Tissue From Mtb Infected B...mentioning
confidence: 99%
“…Thus, in response to certain vaccine candidates against TB, the early induction of IL-17A conveys vaccine-induced protection from Mtb challenge, but in vaccination with other candidates, the cytokine is dispensable [ 8 , 16 ]. Similarly, the increased production of IL-17A in mice with a deficiency of the specific IL-27 receptor subunit IL-27Rα mediated protection against Mtb accompanied by the formation of highly organized granulomas and an accumulation of multifunctional CD4 + T cells in the lung [ 6 , 17 ].…”
Section: Introductionmentioning
confidence: 99%